Pro-angiogenic changes of T-helper lymphocytes in hereditary hemorrhagic telangiectasia - Guilhem, Alexandre; Ciudad, Marion; Aubriot-Lorton, Marie-Hélène; Greigert, Hélène; Cladière, Claudie; Leguy-Seguin, Vanessa; Audia, Sylvain; Samson, Maxime; Bonnotte, Bernard (Frontiers in Immunology, 2023)
Hereditary hemorrhagic telangiectasia (HHT) is a rare inherited disease due to heterozygous loss-of-function mutations on the BMP9/10 pathway (ENG, ACVRL1 or MADH4 mainly). HHT endothelial cells are prone to lose their quiescence, leading to progressive appearance of numerous telangiectases on skin and mucosa (complicated by epistaxis and anemia), and to larger arteriovenous malformations in lungs, liver and brain. HHT is also associated with T lymphocyte abnormalities, which are currently poorly understood. We quantified by flow-cytometry the main T lymphocyte circulating subsets in 40 HHT patients and 20 matched healthy controls. Immunostaining was done on 2 HHT skin telangiectases. Disruptions in T lymphocyte homeostasis was observed, characterized by increases in subsets known to promote angiogenesis: Th2 (1.38% vs 1.15%, p=0.021), Th17 (0.32% vs 0.22%, p=0.019 2) and Treg (4.94% vs 3.51%, p= 0.027). T angiogenic lymphocytes (Tang), defined as CD3+CD31+CXCR4+ T cells, were at similar levels in both groups, but the proportion of VEGF-A+ Tang after stimulation was higher in the HHT group compared to controls (68.2% vs 44.9%, p=0.012). The global HHT T lymphopenia predominantly affected the effector memory T-helper cells (200 vs 270 cells/mm3, p=0.017), and the lymphocytic infiltrate around HHT telangiectases consisted of memory T-helper cells. The Th17 circulating subset was positively correlated with the monthly epistaxis duration (r coefficient: +0,431, p=0.042), prospectively assessed. HHT T-helper lymphocytes are affected by several pro-angiogenic changes, potentially resulting from their recruitment by abnormal endothelial cells. They could constitute a biologically relevant source of VEGF-A and a valuable therapeutic target in HHT.